The impact of breast support garments on fit, support and posture of larger breasted women. (May 2022) - Haworth, Lauren; May, Karen; Janssen, Jessie; Selfe, James; Chohan, Ambreen
Abstract: Due to current measurement, sizing and fitting approaches, poor bra fit is prevalent amongst larger breasted women. The impact of improving bra fit hasn't yet been explored. This pre-clinical study aimed to explore immediate and short-term biomechanical responses to changing breast support garment. Asymptomatic participants (n=24) performed a static standing task, drop jumps and seated typing whilst kinematic data from the breasts and spine were recorded. Three breast support conditions were assessed: Usual, professionally fitted bra in the immediate term (PFB), and the same professionally fitted bra after four weeks wear (PFB28 ). Bra fit assessments were included for both bras. All participants failed the bra fit assessment when wearing the Usual bra and 67% (n=16) failed when wearing the PFB. Less bra fit issues were present in the PFB, resulting in immediate biomechanical changes relating to breast support and spinal posture, yet nothing in the short term (PFB28 ). This research sets the foundations for future work to investigate whether the implementation of better fitting breast support garments can influence musculoskeletal pain amongst larger breasted women, whilst attributing potential improvement of symptoms, objective measures of breast support and spinal posture. Highlights: Use of professional bra fitting services do not guarantee correct bra fit for larger breasted women. Nipple-Sternal-Notch distance may be an appropriate measure of uplift applied to the breast by a bra. Improving bra fit may be useful for prevention/conservative rehabilitation of chronic back pain. Revision of bra design, sizing, and measurement approaches for large breasted women is advised.